PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, PROFITABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN : (Studi Kasus di Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) BTM Batang Tahun 2020-2024) - Setyawati, Misroh; Hidayah, Rini (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the influence of liquidity, solvency, and profitability ratios on the performance of the Baitut Tamwil Muhammadiyah Savings and Loans Cooperative (KSPPS BTM) Batang from 2020 to 2025. This study uses a quantitative approach with multiple linear regression analysis, using secondary data from five years of annual financial reports. The independent variables in this study are liquidity (Cash Ratio), solvency (Debt to Equity Ratio), and profitability (Return on Assets). The dependent variable is financial performance, as measured by operating profit (SHU). The results indicate that partially, only solvency significantly influences financial performance. However, simultaneously, all three variables significantly influence the financial performance of KSPPS BTM Batang. The results of this study provide important insights for company management in formulating more effective and efficient financial strategies.